Victims Before the International Criminal Court: Definition, Participation, Reparation - Safferling, Christoph (Springer eBook Collection, 2021)
Victims before international justice -- International Practice of Victims’ Rights -- Victims’ Participation under the Rome Statute -- Reparation for Victims -- Summary: Victims of International Crimes -- Annex - Victim-Related Relevant Decisions.